Strength ball training - Goldenberg, Lorne, ....- (Champaign : Human Kinetics, 2016)
Who says the best can't get better? The third edition of Strength Ball Training delivers more exercises, programs, assessments, and videos for better results. Preferred by elite athletes, fitness experts, and strength and conditioning specialists, stability and medicine ball exercises are essential to developing core power, strength, balance, coordination, and stability. Strength Ball Training presents those exercises along with instruction and advice on achieving results. Inside you will find assessments to help you determine your current ability level and corrective exercises that address deficiencies. The exercises can be sequenced to create individual programs that target specific regions or enhance total-body performance. You'll learn to incorporate equipment such as cables, bands, and dumbbells for added versatility and increased resistance. And you'll be granted exclusive access to online videos demonstrating the most complex and advanced exercises. Strength Ball Training also includes sample programs with a full array of strength, flexibility, and balance challenges that will test you to your very core.
Includes exclusive acccess to online video library
Keywords: Krachttraining